Ranging behaviour of edible nest swiftlet (Aerodramus sp.) in Kuala Langat district, Selangor, Malaysia - Burhanuddin, Maisarah; Mohd Noor, Hafidzi (Malaysian Society of Applied Biology, 2017)
The edible bird’s nest has been consumed by humans for centuries for its medicinal properties and health benefits. Traditionally, the dried gelatinous coating of the edible-nest swiftlet is boiled together with rock sugar and eaten as a delicacy. However, today, the edible bird’s nest has also been commercialised into health and cosmetic products. Despite the importance of the product, many questions remain within the nest builder, the edible-nest swiftlet (Aerodramus fuciphagus) specifically regarding their ecology and behaviour in nature. The ranging behaviour of the Aerodramus sp., and its foraging areas were studied in the Kuala Langat district. The swiftlets were successfully tagged and tracked using vehicles. The research was conducted from March 2013 to July 2013. It was found that swiftlets had an average core area of 1687.06 ha (16.87 km²), a home range size of 6437.47 ha (64.37 km²) and an average flying distance from their birdhouses which ranged from 2 to 6 km. They were mostly found roaming in open fields, young oil palm plantations and nearby forested areas. Pearson correlation analysis showed that 50% of core feeding range areas and 95% of feeding range areas of the swiftlets correlated negatively with wind velocity (mph) at r = 0.8057, P = 0.0287 and r = 0.820, P = 0.024, respectively. The average flying speed of the swiftlets correlated positively with wind velocity and the correlation was significant (r = 0.8423, P < 0.05).